Hubungan Pemanfaatan Internet Dengan Kinerja Penyuluh Pertanian Pada Kelompok Tani Pangan - Muzakir, A; Hamid, Ernawati; Muchlis, Fuad (JALOW | Journal of Agribusiness and Local Wisdom, 2022)
Research aims 1) Describe the picture of internet utilization in Tanjung Jabung Barat Regency,2) Analyzing the performance level of agricultural extension workers in Tanjung Jabung Barat Regency, and 3) Analyzing the relationship between internet use and the performance of agricultural extension workers in Tanjung Jabung Barat Regency. This research was conducted in Pengabuan and Senyerang sub-districts as many as 20 agricultural extension workers and 85 farmer groups. Data analysis using Spearman rank analysis. The results of the study show that the internet has been used by extension workers. The use of the internet by extension workers to meet the needs of personal information and farmer groups. An indicator of internet utilization in a place is the presence or absence of an internet network, at the research location, the internet network is already available throughout the kelurahan/village. The availability of the network will make it easier for agricultural extension workers to meet the need for information, will affect the duration of extension workers in accessing the internet. The duration of internet use will affect the amount of information obtained, the longer the duration of internet use, the more information will be obtained, and in the end it will affect the use of the internet with the performance of the extension worker. The results of the analysis show that the relationship between internet use and the performance of agricultural instructors has a value of 0.003, where 0.003 < 0.05 so that internet use is significantly related to performance with an error of 1%. The strength of the relationship between the two variables at a value of 0.625** means that it has a strong relationship strength. While the direction of the relationship between the two variables is positive.